Building the Progressive City One Neighborhood at a Time: The Story of the East St. Louis Action Research Project (USA) - Reardon, Kenneth; Raciti, Antonio (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2018)
The article chronicles the economic and social collapse of a once vibrant industrial city located along the banks of the Mississippi River. It describes how powerful deindustrialization, disinvestment, and suburbanization forces undermined the health of the East St. Louis, Illinois economy and municipal government leaving the city’s 40,000 residents without such basic municipal services as: street lighting and garbage collection for eight years. What distinguishes this story is the emergence of a small group of low-income African American women who responded to the failures of their municipal government by self-organizing a “bottom-up, bottom-sideways” planning, and development process. This article describes how these women, with the assistance of students and faculty from the University of Illinois at Urbana-Champaign, worked together to generate more than $200 million in new investment which stabilized their neighborhood and encouraged others to undertake similar resident-led planning efforts. Along the way, this unlikely “partnership” involving grassroots leaders, municipal officials, and university scholars developed a new model of community development. Their empowerment planning approach to urban development integrates key principles and methods of participatory action research (PAR), direct action organizing (DAO), and popular education into a highly effective urban transformation process that has subsequently been replicated in many other economically distressed communities.